2006
DOI: 10.1097/01.pec.0000248683.09895.08
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Oral Dexamethasone in the Emergency Management of Children With Exacerbations of Mild to Moderate Asthma

Abstract: A single dose of oral Dex (0.6 mg/kg) is no worse than 5 days of twice-daily prednisolone (1 mg/kg per dose) in the management of children with mild to moderate asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 19 publications
4
80
0
Order By: Relevance
“…Application of inclusion and exclusion criteria resulted in 6 studies that were included in our analysis (Fig 1). [11][12][13][14][15][16] All of the included studies were performed in EDs and had a mean of 171 participants (range 15-272). All studies but one (Gordon et al 12 ) defined relapse as an unplanned clinic visit, return ED visit, or an unplanned hospital admission related to their initial asthma exacerbation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Application of inclusion and exclusion criteria resulted in 6 studies that were included in our analysis (Fig 1). [11][12][13][14][15][16] All of the included studies were performed in EDs and had a mean of 171 participants (range 15-272). All studies but one (Gordon et al 12 ) defined relapse as an unplanned clinic visit, return ED visit, or an unplanned hospital admission related to their initial asthma exacerbation.…”
Section: Resultsmentioning
confidence: 99%
“…All studies but one (Gordon et al 12 ) defined relapse as an unplanned clinic visit, return ED visit, or an unplanned hospital admission related to their initial asthma exacerbation. Dexamethasone was given as a single IM dose in 3 studies, 12,14,15 as a single oral dose in 1 study, 11 and as multiple oral doses in 2 studies 13,16 (Table1). Included studies were from the United States (n = 5) and Canada (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with mild to moderate exacerbations, a single dose of dexamethasone of 0.6 mg/kg may be similarly effective. 94 Both older and more recent studies have indicated that inhaled corticosteroids are less effective than oral corticosteroids during acute exacerbations in children, 95,96 and systemic corticosteroids should therefore be used for stabilization. 97 …”
Section: Bronchodilatorsmentioning
confidence: 99%
“…Altamimi et al 32 compared a single dose of PO dexamethasone with 5 days of PO prednisolone in a prospective, randomized, double-blind study. Patients with mild to moderate asthma were randomized to receive either dexamethasone or prednisolone in the ED, then discharged with 5 days of placebo or liquid prednisolone, respectively.…”
Section: Oral Dexamethasonementioning
confidence: 99%